Investment Criteria, Productivity, and Economic Development - Galenson, Walter; Leibenstein, Harvey (Quarterly Journal of Economics, 1955)
I. A suggested criterion for investment allocation, 343. — II. The case for high labor productivity in underdeveloped areas, 353; the level of labor productivity in underdeveloped areas, 353; labor productivity and capital allocation, 355; population growth and development, 363; some obstacles to high labor productivity in backward areas, 367. — III. Conclusion, 369.